Nivolumab and Doxorubicin, Vinblastine, and Dacarbazine in early-stage unfavorable Hodgkin Lymphoma: final analysis of the randomized German Hodgkin Study Group Phase II NIVAHL trial - Bröckelmann, Paul Jan; Bühnen, Ina; Meißner, Julia; Trautmann-Grill, Karolin; Herhaus, Peter; Halbsguth, Teresa V.; Schaub, Valdete; Kerkhoff, Andrea; Mathas, Stephan; Bormann, Matthias; Dickhut, Andreas; Kaul, Helen; et al. (Journal of clinical oncology, 2023)
Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. - - In the investigator-sponsored randomized phase II NIVAHL trial for early-stage unfavorable classical Hodgkin lymphoma (HL), two schedules of four cycles of nivolumab, doxorubicin, vinblastine, and dacarbazine followed by 30 Gy involved-site radiotherapy resulted in high complete remission rates and an unprecedented 1-year progression-free survival in 109 patients. In this article, we report the preplanned final analysis conducted three years after the registration of the last patient including long-term safety results. No survival events were observed since the primary analysis, and after a median follow-up (FU) of 41 months, the overall survival was 100% in both treatment groups. The progression-free survival was 98% and 100% in the sequential and concomitant nivolumab, doxorubicin, vinblastine, and dacarbazine treatment groups, respectively. At last FU, the mean forced expiratory pressure in one second was 95.5% (standard deviation 12.7%), the mean diffusion capacity for carbon monoxide adjusted for hemoglobin was 82.8% (standard deviation 15.4%), and the left ventricular ejection fraction was in the normal range in 95% of patients. Hypothyroidism requiring long-term medication occurred in 15% of patients, who were nearly exclusively female (87%). No second primary malignancies occurred, and no patient required corticosteroid treatment at last FU. Patient-reported normalized global quality-of-life score measured by European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire C30 improved over time. This preplanned FU analysis of the largest anti-programmed death protein 1 HL first-line trial to date confirms the outstanding efficacy and relatively favorable safety profile of this therapeutic approach.